Fluorescence and antioxidant activity of heterologous expression of phycocyanin and allophycocyanin from Arthrospira platensis - Shang, Meng-hui; Sun, Jian-fei; Bi, Ying; Xu, Xiao-ting; Zang, Xiao-nan (Frontiers in Nutrition, 2023)
Phycocyanin and allophycocyanin are important active substances in Arthrospira platensis, because of their fluorescent characteristic and antioxidant capacity. In order to solve the problem of insufficient production and inconvenient modification of natural protein, recombinant expression was performed and the fluorescence activity and antioxidant activity was analyzed to meet the demand for phycocyanin and allophycocyanin. A total of seven recombinant strains were constructed in this study, including individual phycocyanin or allophycocyanin, co-expression of phycocyanin-allophycocyanin, and their co-expression with chromophore, and the expression strain for individual chromophore. Different molecular weights of phycocyanin and allophycocyanin were detected in the recombinant strains, which indicated the different polymers expressed. Through mass spectrometry identification, phycocyanin and allophycocyanin may form a dimer of 66kDa and a polymer of 300kDa. The results of fluorescence detection showed that phycocyanin and allophycocyanin combined with phycocyanobilin to show fluorescence activity. The fluorescence peak of recombinant phycocyanin was mainly concentrated at 640nm, which was similar to natural phycocyanin, the fluorescence peak of purified recombinant allophycocyanin was at about 642nm. The fluorescence peak of the co-expressed recombinant phycocyanin-allophycocyanin is located at 640nm, and the fluorescence intensity is between the recombinant phycocyanin and the recombinant allophycocyanin. After purification, the fluorescence peak of the recombinant phycocyanin is more concentrated and the fluorescence intensity is higher, which is about 1.3 times of recombinant phycocyanin-allophycocyanin, 2.8 times of recombinant allophycocyanin, indicating that phycocyanin may be more suitable to be used as fluorescence probe in medicine. The antioxidant capacity was measured by using total antioxidant capacity (T-AOC) and DPPH (2,2’-diphenyl-1-triphenylhydrazino) free radical scavenging method, and the recombinant phycobiliprotein showed antioxidant activity. Phycocyanobilin also has certain antioxidant activity and could enhance the antioxidant activity of phycobiliprotein to a certain extent. Recombinant phycocyanin-allophycocyanin polymer has stronger T-AOC, which is about 1.17-2.25 times that of the other five recombinant proteins. And recombinant phycocyanin has stronger DPPH antioxidant activity, which is about 1.2-2.5 times that of the other five recombinant proteins. This study laid the foundation for the application of recombinant phycocyanin and allophycocyanin in medical detection and drug development.